Factors associated with survival to hospital discharge among patients hospitalised alive after out of hospital cardiac arrest: change in outcome over 20 years in the community of Göteborg, Sweden. Issue 1 (1st January 2003) - Herlitz, J; Bång, A; Gunnarsson, J; Engdahl, J; Karlson, B W; Lindqvist, J; Waagstein, L
Abstract : Objective: To describe the change in survival and factors associated with survival during a 20 year period among patients suffering from out of hospital cardiac arrest and being hospitalised alive. Patients: All patients hospitalised alive in the community of Göteborg after out of hospital cardiac arrest between 1 October 1980 and 1 October 2000 were included. Methods: Patient data were prospectively computerised with regard to factors at resuscitation. Data on medical history and hospitalisation were retrospectively recorded. Patients were divided into two groups (the first and second 10 year periods). Setting: Community of Göteborg, Sweden. Results: 5505 patients suffered from cardiac arrest during the time of the survey. Among them 1310 patients (24%) were hospitalised alive. Survival (discharged alive) was 37.5% during the first part and 35.1% during the second part (NS). The following were independent predictors of an increased chance of survival: ventricular fibrillation/tachycardia as the first recorded rhythm (odds ratio (OR) 3.46, 95% confidence interval (CI) 2.36 to 5.07); witnessed arrest (OR 2.50, 95% CI 1.52 to 4.10); bystander initiated cardiopulmonary resuscitation (OR 2.00, 95% CI 1.42 to 2.80); the patient being conscious on admission to hospital (OR 6.43, 95% CI 3.61 to 11.45); sinus rhythm on admission to hospital (OR 1.53, 95% CI 1.12 to 2.10); and treatment with lidocaine in the emergency department (OR 1.64, 95% CI 1.16 to 2.31). The following were independent predictors of a low chance of survival: age > 70 years (median) (OR 0.65, 95% CI 0.47 to 0.88); atropine required in the emergency department (OR 0.35, 95% CI 0.16 to 0.75); and chronic treatment with diuretics before hospital admission (OR 0.59, 95% CI 0.43 to 0.81). Conclusion: There was no improvement in survival over time among initial survivors of out of hospital cardiac arrest during a 20 year period. Major indicators for an increased chance of survival were initial ventricular fibrillation/tachycardia, bystander cardiopulmonary resuscitation, arrest being witnessed, and the patient being conscious on admission. Major indicators for a lower chance were high age, requirement for atropine in the emergency department, and chronic treatment with diuretics before cardiac arrest.